The SlERF4-9-SlCDF1/3-SlAEC2/SlPIN5 module regulates tomato root morphogenesis - Fan, ZhengFeng; Zhang, Li; Li, SiQi; Pang, ShengQun; Zhang, YiBing; Xu, ChuanQiang; Liu, YuDong; Qi, MingFang (Frontiers in Plant Science, 2025)
AP2/ERF transcription factors regulate plants’ growth, development, and stress responses. In this study, the seed germination rate and seedling growth were reduced in the tomato slerf4-9 mutant. The fresh weight, drought weight, number of primary lateral roots (LRs), average root diameter, and number of root tips were also decreased in the mutant. The findings suggest that SlERF4-9 plays a significant role in root growth and development. The results of RNA-seq analysis of young roots indicated that the mutation of SlERF4-9 did not affect the expression of genes related to auxin biosynthesis or signal transduction, but it did reduce the expression of the auxin efflux carrier genes SlAEC2 and SlPIN5. Moreover, the mutation of SlERF4-9 affected the distribution of auxin in the roots of DR5 × WT and DR5 × slerf4-9 hybrid tomato seedlings. However, the promoters of SlAEC2 and SlPIN5 do not possess the GCC-box or DRE elements, suggesting that SlERF4-9 does not directly regulate their transcription. In addition, the expression levels of the two Cycling DOF Factors (CDFs) SlCDF1 and SlCDF3 decreased in the roots of the slerf4-9 mutant. Moreover, the GCC-box was present in the promoters of SlCDF1 and SlCDF3. Therefore, exploring the regulatory relationships between SlERF4-9, SlCDF1/3, and SlAEC2/SlPIN5 will further our understanding of the molecular mechanisms of tomato root growth and development.